Modeling thermal conductivity of hemp insulation material: A multi-scale homogenization approach. (October 2016) - Nguyen, S.T.; Tran-Le, A.D.; Vu, M.N.; To, Q.D.; Douzane, O.; Langlet, T.
Abstract: The growing awareness of environment protection and climate change have increased the attention on the development of new environmentally-friendly materials. This study will concentrate on the thermal performance of hemp shives which are used as insulation material. A multi-scale homogenization approach accounting for the shape and orientation of pores and particles is developed to model the effective thermal conductivity and anisotropy of this bio-based material. An inverse analysis using the experimental thermal conductivity data of dry shives in bulk allows determining the thermal conductivity of the solid phase of hemp shiv, which is difficult to measure. The latter is then used in the multi-scale model to estimate the overall thermal conductivity of a single hemp shiv particle and hemp insulation material as functions of the temperature and moisture content. The effect of hemp shiv particle's size on the effective thermal conductivity and its anisotropy will be also discussed. Highlights: A multi-scale homogenization approach to model the effective thermal conductivity and anisotropy of hemp insulation material is developed. Thermal conductivity of hemp insulation material increased linearly with increasing saturation degree, density and temperature. Thermal conductivity of hemp insulation material is significantly affected by the moisture content, the density and the orientation of hemp particles. The model given can be used to optimize the thermal performance of bio-based insulation materials that have similar internal structures as hemp.